2021
DOI: 10.3390/agronomy11040759
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Age-Dependent Effects of Boron Toxicity in Two Cucumis melo Varieties

Abstract: Boron (B) is an essential nutrient for plant growth and development, exhibiting extremely narrow margins between deficiency and toxicity. B toxicity is devastating for productivity and apparent for a continuously increasing part of agricultural land, under the influence of on-going climate change. In this study, the effects of increased B supply (by using H3BO3) were addressed by examining critical physiological responses of young and mature leaves, which were devoid of toxicity symptoms, in two melon varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Moreover, low temperature (10 • C for 24 h) greatly induced several genes encoding for 4CL isoenzymes that catalyze the conversion of 4-coumaric acid, caffeic acid, and ferulic acid to their corresponding CoA esters. Hence, it can be deduced that channeling the metabolic flow towards the production of multiple phenylpropanoid metabolites from structural molecules (e.g., lignin) to metabolites with strong antioxidant activity contributes to the plasticity of the metabolic pathway in the ever-changing environmental stimuli [12,13,[40][41][42]. In tomatoes, cold stress (4 • C for 24 h) significantly increased transcription of 4CL genes [43], while the 4CL2 isoenzyme was recently associated with increased flavonoid production and antioxidant activity [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low temperature (10 • C for 24 h) greatly induced several genes encoding for 4CL isoenzymes that catalyze the conversion of 4-coumaric acid, caffeic acid, and ferulic acid to their corresponding CoA esters. Hence, it can be deduced that channeling the metabolic flow towards the production of multiple phenylpropanoid metabolites from structural molecules (e.g., lignin) to metabolites with strong antioxidant activity contributes to the plasticity of the metabolic pathway in the ever-changing environmental stimuli [12,13,[40][41][42]. In tomatoes, cold stress (4 • C for 24 h) significantly increased transcription of 4CL genes [43], while the 4CL2 isoenzyme was recently associated with increased flavonoid production and antioxidant activity [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the phenylpropanoid biosynthetic pathway is a cross response to several environmental perturbations (reviewed in Šamec et al [11]), and is generally upregulated under either abiotic or biotic stress. In plants facing adverse conditions, the accumulation of phenolic compounds through activation of this pathway has been generally associated with enhanced stress tolerance [12][13][14]. The induced resistance has been related to the wide range of polyphenol functions, principally consisting of reactive oxygen species (ROS) scavenging ability (thus oxidative stress alleviation) and strong antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…This has been a major cause of soil and water pollution, soil erosion, nutrient imbalance, lessened agrobiodiversity, decreased soil fertility, and low water holding capacity, and has caused disturbances in natural soil flora and fauna [ 6 ]. The use of excess nutrients is polluting soil, and water scarcity makes the condition worse [ 7 ]. It was reported that a large portion of synthetic nutrients are not absorbed by plants, and instead run off from the fields and become integrated into water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal phenotype can be caused by either abiotic or biotic stress. The former is caused, for instance, by lack or excess of nutrients or water [51]. The latter can be caused by fungi, bacteria, and viruses.…”
Section: Visual Explanationsmentioning
confidence: 99%